1990
DOI: 10.1002/art.1780330715
|View full text |Cite
|
Sign up to set email alerts
|

Elevated substance p and accelerated cartilage degradation in rabbit knees injected with interleukin‐1 and tumor necrosis factor

Abstract: Cytokines, interleukin-1 (IL-I), tumor necrosis factor a, and the neurotransmitter, substance P, have been implicated in the pathogenesis of arthritis because they stimulate synovial cells to secrete prostaglandin E, and collagenase in vitro. We investigated in vivo changes in intraarticular substance P and the degradation of cartilage proteoglycan in response to intraarticular cytokine injections in rabbits. Twenty-four hours after a single injection of 10 ng, 30 ng, or 100 ng of recombinant human &la (rHuIL-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

1992
1992
2003
2003

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(39 citation statements)
references
References 25 publications
2
37
0
Order By: Relevance
“…Intra-articular injections of TNF and IL-1 cause an in¯ux of neutrophils into the joint and synovitis similar to that seen in experimental arthritis, but only IL-1 results in marked depletion of the cartilage matrix (Dingle et al, 1987b;Van De Loo & Van Den Berg, 1990;Henderson & Pettipher, 1989;O'byrne et al, 1990). In vitro, TNF is also less potent Berg et al, 1994;Williams et al, 1992;Piguet et al, 1992;Thorbecke et al, 1992).…”
Section: Introductionmentioning
confidence: 91%
“…Intra-articular injections of TNF and IL-1 cause an in¯ux of neutrophils into the joint and synovitis similar to that seen in experimental arthritis, but only IL-1 results in marked depletion of the cartilage matrix (Dingle et al, 1987b;Van De Loo & Van Den Berg, 1990;Henderson & Pettipher, 1989;O'byrne et al, 1990). In vitro, TNF is also less potent Berg et al, 1994;Williams et al, 1992;Piguet et al, 1992;Thorbecke et al, 1992).…”
Section: Introductionmentioning
confidence: 91%
“…In addition, recent findings indicate that LP, or at least its N-terminal domain, may function as a growth factor up-regulating the synthesis of aggrecan and type II collagen in cartilage (21)(22)(23)(24).…”
Section: In Brainmentioning
confidence: 99%
“…In addition, our laboratory has recently demonstrated a novel mechanism by which substance P may augment inflammatory responses by dramatically diminishing the production of the immunosuppressive cytokine, TGF-␤1, from macrophages stimulated with LPS or IFN-␥ (22). Furthermore, compelling evidence for the importance of substance P and its receptor in inflammatory events in vivo comes from studies that have identified increased substance P levels (23)(24)(25)(26)(27)(28) or substance P receptor expression (29 -31) at sites of inflammation. More recently, studies have demonstrated greatly reduced inflammatory responses in genetically manipulated mice devoid of substance P/substance P receptor interactions (32,33), providing further evidence for this neuropeptide as a proinflammatory mediator in vivo.…”
Section: Il-4 and Ifn-␥ Up-regulatementioning
confidence: 99%